Facebook and its uses and gratifications: a study of Palestinian students at a Public University in Malaysia / Bader Alakklouk and Aida Mokhtar. - Alakklouk, Bader; Mokhtar, Aida (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2017)
This study explores the uses and gratifications theory on the use of Facebook among Palestinian students at a public university in Malaysia. The theory posits that individuals actively choose media channels or media content to satisfy their needs. In-depth interviews were conducted among 12 heavy users of facebook. These participants comprise Palestinian students of a public university in Malaysia. As it is, Facebook is a convenient platform to express ideas and opinions on the Palestine crisis making it popular amongst Palestinian users particularly with the PalestineIsrael conflict that is taking place now in the West Bank, Gaza Strip and Jerusalem. The findings of the study identify the needs gratified by Facebook: connecting, source of news and information, freedom of expression, entertainment and academic purposes. The reasons why Facebook gratifies the public university’s Palestinian students’ needs is because Facebook is perceived as a convenient platform, is a famous social networking site (SNS), provides entertainment and allows the freedom of expression. The participants pointed out three improvements that are required from Facebook: improving the privacy of users, cutting advertisements and allowing more freedom of expression.